2011
DOI: 10.1371/journal.pone.0026075
|View full text |Cite
|
Sign up to set email alerts
|

Kallikreins 5, 6 and 10 Differentially Alter Pathophysiology and Overall Survival in an Ovarian Cancer Xenograft Model

Abstract: Human tissue kallikreins (KLKs) are members of a multigene family of serine proteases aberrantly expressed in many cancer types. In ovarian cancer, 12 KLKs are upregulated, and of those KLK5, 6 and 10 have been the focus of investigations into new diagnostic and prognostic biomarkers. However, little is known about the contributions of KLK5, 6 and 10 to ovarian cancer pathophysiology.In this study, a panel of 13 human ovarian cancer cell lines was screened by ELISA for secretion of KLK5, 6, 8, 10, 13, and 14. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Thus, conceivably the KLK4 functional blocking antibody is also inhibiting non proteolytic KLK4 effects although the data from the use of the KLK4 selective active site SFTI inhibitor clearly indicates that there is a significant proteolytic component to this effect as well. Consistent with this argument, a recent study showed that catalytically inactive KLK10, another member of this gene family, displayed a role as a tumor suppressor on ES2 ovarian cancer cells both in vitro and in vivo [58]. An earlier study revealed that two prostate specific antigen (PSA, also known as KLK3) blocking antibodies, one inhibiting enzymatic activity and one not affecting catalytic activity, both inhibited the biological function of this kallikrein, suggesting that PSA also has an alternative function via protein-protein interaction [59].…”
Section: Discussionmentioning
confidence: 63%
“…Thus, conceivably the KLK4 functional blocking antibody is also inhibiting non proteolytic KLK4 effects although the data from the use of the KLK4 selective active site SFTI inhibitor clearly indicates that there is a significant proteolytic component to this effect as well. Consistent with this argument, a recent study showed that catalytically inactive KLK10, another member of this gene family, displayed a role as a tumor suppressor on ES2 ovarian cancer cells both in vitro and in vivo [58]. An earlier study revealed that two prostate specific antigen (PSA, also known as KLK3) blocking antibodies, one inhibiting enzymatic activity and one not affecting catalytic activity, both inhibited the biological function of this kallikrein, suggesting that PSA also has an alternative function via protein-protein interaction [59].…”
Section: Discussionmentioning
confidence: 63%
“…Alternatively, expression of KLK protein isoforms with no protease activity may indicate that KLKs have other functions, at least in human. Indeed, KLK10 has been reported to lack trypsin-like enzymatic activity in ovarian ascites fluid [54], although overexpression of KLK10 is associated with lessened aggressivity of ovarian cancer [55]. Also, it has been reported that the proteolytic activity of PSA is not necessary for its role in generating reactive oxygen species (ROS) in prostate cancer [56]; however, more recent reports indicate that the enzymatic activity of PSA is linked to inhibition of ROS scavenging [57] and to the growth of prostate tumors [58].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we show that inhibition of EMTs may underlie the cancer suppressing effects of KLK5. Recently, it was reported that reactivation of KLK5 reverted the malignancy of ES-2 ovarian cancer cells [26]; however, no mechanistic insight has been provided. A novel and very intriguing finding of our study is that expression of KLK5 is associated with alteration in several genes encoding enzymes and regulatory proteins of the mevalonate pathway, including the induction of SREBF1 transcription factor.…”
Section: Discussionmentioning
confidence: 99%